Inflammatory mediators profile in patients hospitalized with COVID-19: A comparative study - Tufa, Abdisa; Gebremariam, Tewodros Haile; Manyazewal, Tsegahun; Getinet, Tewodros; Webb, Dominic-Luc; Hellström, Per M.; Genet, Solomon (Frontiers in Immunology, 2022)
Abnormal cytokine and chemokine concentrations during SARS-CoV-2 infection may represent disease severity. We aimed to assess plasma cytokine and chemokine concentrations in patients with SARS-CoV-2 in Addis Ababa, Ethiopia. In this study, 260 adults: 126 hospitalized patients with confirmed COVID-19 sorted into severity groups: severe (n=68) and mild or moderate (n=58), and 134 healthy controls were enrolled. We quantified 39 plasma cytokines and chemokines using multiplex ELISA. Spearman rank correlation and Mann-Whitney U test were used to identify mechanistically coupled cytokines/chemokines and compare disease severity. Compared to healthy controls, patients with COVID-19 had significantly higher levels of interleukins 1ɑ, 2, 6, 7, 8, 10 and 15, C-reactive protein (CRP), serum amyloid A (SAA), intercellular adhesion molecule 1 (ICAM-1), vascular cell adhesion protein 1 (VCAM-1), IFN-γ-inducible protein-10 (IP-10), macrophage inflammatory protein-1 alpha (MIP-1ɑ), eotaxin-3, interferon-gamma (IFN-Ƴ), tumor necrosis factor-ɑ (TNF-ɑ), basic fibroblast growth factor (bFGF), placental growth factor (PlGF), and fms-like tyrosine kinase 1 (Flt-1). Patients with severe COVID-19 had higher IL-10 and lower macrophage-derived chemokine (MDC) compared to the mild or moderate group (P<0.05). In the receiver operating characteristic curve, SAA, IL-6 and CRP showed strong sensitivity and specificity predicting the severity and prognosis of COVID-19. Greater age and higher CRP had a significant association with disease severity (P<0.05). Our findings reveal that CRP, SAA, VCAM-1, IP-10, MDC and IL-10 levels are promising biomarkers for COVID-19 disease severity, suggesting that plasma cytokines/chemokines could be used as warning indicators of COVID-19 severity, aid in COVID-19 prognosis and treatment.